PENGEMBANGAN PRODUK “PUKHI” PUDING UBI UNGU DAN KACANG HIJAU SEBAGAI SNACK PASIEN DIABETES MELLITUS TIPE 2 - Nirma Maretasari; Fitria, Mona; Isdiany, Nitta; Suparman, Suparman (Jurnal Gizi dan Dietetik, 2025)
The 2023 Indonesian Health Survey (SKI) showed that the prevalence of diabetes mellitus (DM) diagnosed by doctors in Indonesia was 2.2%.  Dietary regulation, particularly the intake of nutritious snacks that are high in fibre, low in sugar, and possess a low glycaemic index, is crucial for the prevention and management of type 2 diabetes mellitus.  Purple sweet potatoes and mung beans are local foods rich in complex carbohydrates, low glycaemic index, vegetable protein, fibre, and antioxidants.  This study aims to evaluate the impact of purple sweet potato and mung bean formulations on the quality of the snack "PUKHI" (purple sweet potato and mung bean custard), focusing on organoleptic properties and nutritional value.  The experimental study design employed three formulations: F1 (75%:25%), F2 (65%:35%), and F3 (55%:45%).  Organoleptic evaluations were conducted by 15 semi-trained panellists, revealing that F2 received the highest overall score (average 6.1).  The Kruskal-Wallis test indicated no impact of various purple sweet potato and mung bean formulations on taste, colour, texture, and overall quality; however, a significant variation in scent was observed.  The nutritional composition of the optimal formula (F2) per 150 grammes comprised 162.8 kcal of calories, 7 g of protein, 4.1 g of fat, 27.3 g of carbohydrates, and 4.2 g of fibre, aligning with the requirements of DM patients.  The cost per serving was IDR 5,366, representing a 46.6% reduction compared to commercial items. This product is recommended as a snack for diabetes mellitus patients and can be further refined to improve taste and texture.